Tax Morale and its Drivers: Empirical Evidence from Ghana - Ntiamoah, Jones Adjei; Arhenful, Peter; Owusu Kwaning, Collins; Asare, Joseph (Journal of Economics and Behavioral Studies, 2023)
Using the binary logistic regression model, this study analyzes the statistical relationships between tax morale and its drivers as developed by the World Values Survey (WVS) on 1,552 respondents in Ghana between 2010 and 2014. The findings show that age has a significant positive relationship with tax morale, whereas participation in national-level elections also has a significant positive relationship with tax morale. Secondary education and above have a positive relationship with tax morale, but the relationship is negative below secondary education. One’s employment status has a positive but insignificant relationship with tax morale, but income factors have a negative relationship. Confidence in government and parliament has a positive but insignificant relationship with tax morale. Finally, preference for the redistribution of wealth has a significant positive relationship with tax morale, while trust in others has an insignificant positive relationship with tax morale. The study provides country-specific drivers of tax morale (with expanded variables) and their relationships with tax morale in direct response to a suggestion by Daude, Gutiérrez, & Melguizo in their study in 2012 and as an improvement upon a similar study conducted in Ghana by Ibrahim, Musah, & Abdul-Hanan in 2015.